Wasiat Wajibah Terhadap Anak Angkat Pada Hukum Islam - Gesa Gisha meira (SAMAWA, 2024)
AbstractThis research discusses the concept of "Wasiat Wajibah" (compulsory will) regarding adopted children within the Compilation of Islamic Law (KHI) in Indonesia. This is based on the absence of laws resulting in a legal vacuum in the relationship between adoptive parents and adopted children. Islamic law states that adopted children are not entitled to inherit anything from their adoptive parents, and thus, Islamic law suggests "wasiat wajibah" as a solution. The aim of this research is to establish, in accordance with Islamic law, how the inheritance is distributed to adopted children. The research method used is a qualitative approach with a literature review methodology and inductive content analysis. The results show that "Wasiat Wajibah," although not explicitly mentioned in the Quran or Hadith, is regulated in the KHI, granting the right for adopted children to receive "wasiat wajibah" from their adoptive parents, and vice versa. However, this practice faces challenges, especially the disagreement from biological heirs.Keywords: Adopted Children, Islamic Law, Wasiat Wajibah